A Survey of Music Therapy Students' Perceived Stress and Self-Care Practices. (8th April 2019) - Moore, Carolyn; Wilhelm, Lindsey A
Abstract: High levels of stress and burnout are common among professional music therapists and researchers suggest that guidance related to self-care during clinical training may influence professional success and strain. Currently, little is known about music therapy students' perceived stress and levels of self-care engagement. The purpose of this study was to examine music therapy students' perceived stress levels and self-care practices to inform future research in this area. Music therapy students ( n = 371) who were currently enrolled in an academic degree program for music therapy within the United States completed this study. Instrumentation included Perceived Stress Scale and a researcher-modified Student Self-Care Scale (SSCS). Academic program directors distributed the online survey to students. Results indicated that both scales had adequate-to-good internal consistency. An exploratory factor analysis of the SSCS revealed that music therapy students' self-care includes eight factors related to academic and personal self-care practices. The average level of perceived stress reported across music therapy students is higher than previously reported levels for adults in the United States. More specifically, undergraduate music therapy students report higher perceived stress than undergraduate students in general. Lower frequency of self-care engagement, particularly in regard to self-awareness and physical self-care practices, was associated with higher levels of perceived stress. This study provides previously unreported student data of interest to educators and supervisors in music therapy. Continued investigations should focus on the music therapy students' experience and educators' concerns, both of which may generate new curricular approaches to addressing stress and self-care.